PENGETAHUAN REMAJA TENTANG PENDEWASAAN USIA PERKAWINAN DI WILAYAH KAMPUNG KB DESA SUMBER KARANG DLANGGU MOJOKERTO - Silfiyah; Kartiningrum, Eka Diah; Henry Sudiyanto (MEDICA MAJAPAHIT, 2023)
Pregnancy, childbirth, and postpartum difficulties are frequently brought on by early marriage. Raising the marriageable age is one strategy for solving this issue. The goal of this study was to describe what teenagers in Kampung KB, Sumberkarang Village, Dlanggu Mojokerto knew about the legal age of marriage. This study is an empirical survey. 35 youths made up the study's sample, which consisted of 118 adolescents between the ages of 16 and 18. Validity and reliability of the information gathered through questionnaires were examined, and descriptive analysis was then performed. The findings indicated that the majority of respondents were fully informed. The understanding of adolescents regarding the age of marriage is greatly influenced by information sources including videos, brochures, and booklets.